Beneficial effects of dietary β-glucan on growth and health status of Pacific white shrimp Litopenaeus vannamei at low salinity. Issue 91 (August 2019) - Li, Huifeng; Xu, Chang; Zhou, Li; Dong, Yangfan; Su, Yujie; Wang, Xiaodan; Qin, Jian G.; Chen, Liqiao; Li, Erchao
Abstract: An 8-week trial was conducted to evaluate the effect of dietary β-glucan supplement (0, 0.01%, 0.02%, or 0.04%) on growth and health of Pacific white shrimp Litopenaeus vannamei at low salinity of 3 practical salinity unit (psu). The L. vannamei fed 0.02% and 0.04% β-glucan gained more weight and showed higher activities of protease, amylase, superoxide dismutase, and glutathione peroxidase in the intestine than in the control (0% β-glucan). The L. vannamei fed 0.04% β-glucan had a higher condition factor than those fed the control diet. Amylase activity in the hepatopancreas of L. vannamei fed 0.02% β-glucan was higher than those fed the control diet. Dietary β-glucan supplement increased the mRNA expressions of Toll-like receptor, myostatin, immune deficiency or heat shock protein 70, but decreased the mRNA expressions of tumor necrosis factor-α and C-type lectin 3 in both hepatopancreas and intestine. The response of intestine microbiota in L. vannamei fed 0.04% β-glucan was further compared to the control. The 0.04% β-glucan supplement reduced richness and diversity of the intestinal microbial community as indicated by the low values of Chao1 estimator, ACE estimator, Simpson index and Shannon diversity index. Abundances of Bacillus, Chitinibacter, Geobacillus and Vibrio in the intestine increased, while Flavobacterium, Microbacterium and Mycobacterium decreased significantly in L. vannamei fed 0.04% β-glucan compared to the control. This study indicates that dietary β-glucan supplement at 0.02%–0.04% can significantly improve digestibility, antioxidant capacity and immunity in L. vannamei, and thus improve growth performance and survival at low salinity. These beneficial effects of β-glucan probably are related to the dominance of probiotics over potential pathogens in the intestine. Highlights: Dietary 0.02%–0.04% β-glucan improved L. vannamei growth under low salinity. Dietary 0.02%–0.04% β-glucan enhanced shrimp capacity of digestion, antioxidant and immunity. β-glucan shaped L.vannamei gut microbiota through increasing diversity and richness of probiotics.